PROTEIN SECURITY IN ANIMAL HUSBANDRY: CHALLENGES OF WAR AND SOLUTIONS - Позняковський, Юрій; Куриленко, Юрій; Гутий, Борис; Сичов, Михайло; Ільчук, Ігор; Осадча, Юлія; Голубува, Тетяна; Борщенко, Людмила; Боярчук, Сергій (SWorldJournal, 2025)
The article presents a comprehensive scientific and practical analysis of ensuring protein security for farm animals in Ukraine under wartime conditions and during the period of post-war recovery. The material is based on a broad synthesis of contemporar